Workplace Learning in Nepal Through the Lens of Employers, Principal, and Students - Paudel, Prakash Kumar (Dhaulagiri Journal of Sociology and Anthropology, 2024)
Workplace learning opportunities are considered to enhance an individual's occupation-related skills through work interaction. Workplace learning has become part and parcel of Nepal's policies in the last few decades. Internships and On the Job Training (OJT) have remained consistently a mode of workplace learning, but more recently, attempts have been made to execute dual vet apprenticeships. Nevertheless, studies in Nepal show a lack of well-built collaboration between education providers and employers in managing workplace learning. Furthermore, issues include a lack of access to and availability of relevant workplace learning opportunities. This paper discusses Nepal's workplace learning situation based on shared experiences by its actors, employers, Technical and Vocational Education and Training (TVET) providers, and students. The study uses five premises of workplace learning: learning is part of everyday life, it is spontaneous without a structured curriculum, learners need guidance and backing, an equitable opportunity to learn in a respectful environment, and integrating workplace learning with school learning proposed by Billett (2001) as a theoretical framework. The case study method suggested by Yin (2018) was used to explore their experiences. Twelve interviews, four from each group, employers, technical school principals, and students, were conducted to understand their views on workplace learning. Interview guidelines were followed for prolonged engagement in the field. The study's findings showed a lack of collaboration and preparedness among employers and TVET institutions for managing workplace learning. Workplace learning has become less of a priority for employers and TVET providers and is a neglected agenda.